The Influence of Middle East Islamic Movement on the Extremist Thought in Malaysia - Nasir, Badlihisham Mohd (TAWARIKH, 2011)
ABSTRACT: Radicalism is not an entirely new issue in the history of the Islam. It has been an issue raised by the Khawarij group and now re-surfaced in the form of the neo-Khawarij. However, it is not quite appropriate to quickly jump to the conclusion that all Islamic movements are similar to Khawarij. Some of the concepts used by these movements, such as Hakimiyyah liLlah, have been discussed by earlier scholars before. However, many factors have emerged in recent years that have caused the interpretation to deviate from the truth. While, it is obvious that there are some similarities between PAS in Malaysia and the Ikhwan in Egypt, in terms of their radical approach and inspiration, the latter is not directly involved in the militant movement such as the Takfir wa al-Hijrah and al-Maunah. This paper tries to address this issue by first looking at the social and religious background leading to the rise of radical movements in Islam in the Middle East. It will also examine the main concern of these movements and in what way they have influenced the thinking of some Islamic movements in Malaysia.Â Â Â  KEY WORDS: Islamic movement, Middle East, extremist thought, Malaysia, modern society, and globalization.===About the Author: Dr. Badlihisham Mohd Nasir is a Lecturer at the Department of Dakwah and Leadership, Faculty of Islamic Studies UKM (National University of Malaysia), 43600 UKM Bangi, Selangor Darul Ehsan, Malaysia. He can be reached at: aspensi@yahoo.comHow to cite this article? Nasir, Badlihisham Mohd. (2011). âThe Influence of Middle East Islamic Movement on the Extremist Thought in Malaysiaâ in TAWARIKH: International Journal for Historical Studies, Vol.3(1) October, pp.31-46. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 25, 2011); Revised (September 28, 2011); and Published (October 28, 2011).